Effect of Job Characteristics, Motivation, Andwork Discipline on Employee Satisfaction PT. Indonesian Port IV (Persero) Balikpapan Branch - Didik Hadiyatno; Tutik Yuliani; Dwi Martiyanti (Budapest International Research and Critics University, 2022)
The purpose of this study was to examine the effect of the variable job characteristics, motivation, and work discipline on the variable job satisfaction of employees of PT. Pelabuhan Indonesia (Persero) IV Balikpapan Branch, using a sample of 124 people. The analytical tool used is multiple linear regression and a hypothesis testing tool, namely the t test. As for the results of the analysis and the results of hypothesis testing, it was found that Job Characteristics, Motivation, and Work Discipline simultaneously proved to have a significant influence on the variable Job Satisfaction of Employees of PT. Pelabuhan Indonesia (Persero) IV Balikpapan Branch. And the test results partially show that the three independent variables are Job Characteristics, Motivation, and work discipline proved to all show a significant effect on job satisfaction of employees of PT. Pelabuhan Indonesia (Persero) IV Balikpapan Branch.